Subcutaneous Endometriosis after Cesarean Section : A Case Report - Tansil, Tan, Ardio Rizky; Savitri, Irma; Rambulangi, John (Faculty of Medicine, Hasanuddin University., 2023)
Introduction and importance: Endometriosis is a condition in which both the stromal tissue and the functional endometrial glands are observed outside the uterine cavity. Endometriosis can be found in pelvic organs and extra-pelvic. Subcutaneous Endometriosis is a condition which may occur after surgical procedures such as cesarean section. Presentation of case: We report a 37-year-old female patient who had undergone two cesarean sections, presented with cyclic hypogastric pain and vaginal bleeding. Cyclic bleeding also occurred from the cesarean section scar since 1 year ago. Total abdominal hysterectomy, right salpingooophorectomy, left salpingectomy and wide excision of the scar were performed. Histopathology results of stromal tissue and functional endometrial glands on subcutaneous part of the skin were found. Discussion: The incidence of subcutaneous endometriosis can occur months to years after the surgical procedure with an average of about 30 months. Complaints in patients are usually in the form of a painful and enlarged abdominal mass, especially during menstruation. In establishing the diagnosis of subcutaneous endometriosis, the gold standard is pathological examination. The main management of this subcutaneous endometriosis case is a wide excision procedure by performing excision and providing a minimum clearance of 1 cm. Conclusions: Subcutaneous endometriosis is extrapelvic endometriosis, which is mainly caused by surgery, one of which is cesarean section. Establishing a definite diagnosis of subcutaneous endometriosis is difficult without any pathological examination. The main management of subcutaneous endometriosis is wide excision with a margin of 1 cm to prevent recurrence of this disease.